Analysis of the Impact of Sharia Regulations on Halal Trade in Southeast Asia - Maharatna Shifa Nurizka; Mohamad Sobrun Jamil; Faizah; Badrus Sholeh; Ansori (Mahkota Science Publishers, 2025)
This study aims to uncover the underlying narrative behind Sharia regulations, namely that regulations never stand alone but are always the result of a complex interplay between political, economic, religious, and social interests. Using library research and an interdisciplinary approach, this study makes a significant contribution to formulating a halal regulation model that can overcome the challenges of standard harmonisation, small business empowerment, consumer protection, and opening up opportunities for fairer regional and global cooperation. The results show that Sharia regulations in halal trade in Southeast Asia have created complex dynamics. On the one hand, these regulations offer significant potential for economic growth, innovation, and the strengthening of regional identity; on the other hand, they cause fragmentation, exclusion, and challenges to fairness in practice. To avoid being trapped in the logic of protectionism or narrow identity politics, countries in the region are required to reformulate the halal governance paradigm to be more collaborative, inclusive, and transparent, prioritising standard harmonisation and equal access for all business actors across religions and countries. Only through such constructive measures can Southeast Asia's halal industry develop into a global force that is not only economically beneficial but also promotes solidarity, justice, and exemplary social integration amid its diverse population.